Effects of buflomedil and pentoxifylline on hamster skin-flap microcirculation: prediction of flap viability using orthogonal polarization spectral imaging - Mota, Denise Salles Coelho da (2009)
OBJECTIVE: This study investigated the effects of buflomedil and pentoxifylline, both of which are used in reconstructive surgery of hamster skin flap microcirculation, and evaluated the skin flap survival rate by orthogonal polarization spectral imaging. METHOD: Twenty-four adult male Syrian golden hamsters were divided into three groups: a control (C, 0.1 ml 0.9% saline), buflomedil (B, 3 mg/kg/day), and pentoxifylline group (P, 14.5 mg/kg/day). Treatments administered intraperitoneally were initiated 1 hour before skin flap preparation and continued for 7 days post-operatively at 12-hour intervals. Preparations (skin flaps) were divided into 12 fields, which were organized into six bands. Functional capillary density (FCD, in mm/mm²), distance from the skin flap base to blood flow cessation (Dist with flow, in cm), percentage of viable skin (VA, in%), and qualitative analysis of blood flow by orthogonal polarization spectral imaging were performed at 1 and 24 hours and on the seventh post-operative day. RESULT: Bands IV, V, and VI presented no flow independent of time. The functional capillary density group B was higher than that of groups C and P, primarily after 24 hours. All groups showed an increase in D with time but reached similar final distances (C = 2.73, B = 2.78 and P = 2.70 cm). Moreover, the percentage of viable areas remained at approximately 50%. The orthogonal polarization spectral imaging was useful to assess viability by counting fields with and without blood flow. CONCLUSIONS: Functional capillary density values were higher in the buflomedil group compared to the control and pentoxifylline groups in this model. Functional capillary density did not influence D or the percentage of VA, and the technique showed favorable potential to assess/predict the viability of skin flaps within 1 h after surgery.